The Effect of Liquidity and Solvency Ratios on Financial Performance at PT. Pegadaian (Persero) - Thaliya, Anna Bella; Pratiwi, Aliah; Huda, Nurul (Devitara Innovations, 2025)
This study examines the effect of liquidity and solvency ratios on the financial performance of PT Pegadaian (Persero), focusing on Return on Equity (ROE) as the profitability indicator. The independent variables analyzed are Quick Ratio (QR), Debt to Assets Ratio (DAR), and Debt to Equity Ratio (DER). Using a quantitative associative approach, the study employs secondary data from annual financial statements of PT Pegadaian (Persero) for the period 2014–2023. Data were analyzed using multiple linear regression, supported by classical assumption tests, correlation, and determination coefficient analysis. The results indicate that QR, DAR, and DER, both individually and simultaneously, do not significantly influence ROE. This suggests that liquidity and solvency are not the primary determinants of the company’s profitability, with operational efficiency, product innovation, and marketing strategies likely playing a more dominant role. These findings imply that management should maintain financial ratio stability while emphasizing business strategies that enhance profitability. Future research is recommended to expand the study period and sample, incorporate additional financial variables such as ROA, NPM, Current Ratio (CR), and Operating Cash Flow, and utilize more comprehensive analytical methods, including panel data regression or comparative analysis with similar financial service companies.